Evaluasi Peningkatan Kesiapsiagaan Bencana Melalui Metode Indoor Disaster Preparedness Simulation Pada Anggota KSR Jurusan Keperawatan Poltekkes Kemenkes Surakarta - Addi Mardi Harnanto ((JKG) Jurnal Keperawatan Global, 2016)
Abstract: Disaster Preparedness, Disaster Preparedness Indoor Simulation, Volunteer Corps (KSR). The entire people of Indonesia are expected to prepare for disasters. This is done because Indonesia is a country with a fairly high vulnerability to disasters. All elements of society is obliged to make successful of disaster preparedness program. In terms of disaster preparedness, society was divided into groups of masyarakat terlatih, awam khusus and awam. Surakarta Health Polytechnic has been successfully empower youth element as health volunteers through disaster preparedness training activities incorporated in the activities of KSR Unit Jurusan Keperawatan Poltekkes Kemenkes Surakarta. The activities carried out periodically and continuously in the implementation of the program, including disaster preparedness. Purpose to evaluate the increase in disaster preparedness through disaster preparedness indoor simulation method at KSR Unit Jurusan Keperawatan Poltekkes Kemenkes Surakarta. The study was comparative experimental study design with one group pretest-posttest with cross sectional approach. The population in this study were all members of KSR Unit Jurusan Keperawatan Poltekkes Kemenkes Surakarta (150 people). The average increase in value between pretest and posttest is 1.31. T test results that the value t = 17.480 > t table (0.05, df 14) = 1,761 with a 95% confidence level showed α = 0.00 <0.05. There was a significant increase in disaster preparedness through disaster preparedness indoor simulation method in KSR Unit Jurusan Keperawatan Poltekkes Kemenkes Surakarta.